Implementation of Risk Management in The Medical Records Work Unit Reviewed From National Standards For Hospital Accreditation Through A Systematic Literature Review Approach - Khairunnisa Khairunnisa; Nina Rahmadiliyani (Syntax Corporation Indonesia, 2024)
The hospital, there is no denying the possibility of unwanted or unexpected negative impacts in work activities, one of which is in the medical records work unit. The aim of the research is to determine the implementation of risk management in the medical records work unit in terms of the National Hospital Accreditation Standards. The research method used was a Systematic Literature Review with a search strategy using Google Scholar results criteria with the keywords